FRI0384 Safety and efficacy of oral cyclophosphamide long-term therapy in systemic sclerosis: experience of a single-centre. (23rd January 2014) - Vacca, A.; Garau, P.; Porru, G.; Calvisi, S.; Ibba, V.; Piga, M.; Floris, A.; Cauli, A.; Mathieu, A.
Abstract : Background: Interstitial lung disease (ILD) is very common in systemic sclerosis (SSc) and represents the leading cause of death. Despite its toxicity, cyclophosphamide (CYC) remains one of the most effective therapy. However, limited data about optimal dosage, duration therapy and best way of administration are available. It has been suggested that a prolonged CYC regimen might be more effective than a shorter course. Objectives: To evaluate safety and response to oral long-term treatment with CYC in combination with low or medium steroids dose in patients with ILD-SSc. Methods: Twenty two patients with ILD-SSc treated with oral CYC, were retrospectively included in this study. A complete clinical examination, included evaluation of European disease activity score and Mesdger' severity scale score, high-resolution (HRCT) scan, pulmonary function tests (PFTs) were performed before starting therapy, and annually therefore during 10 years of follow-up [86.6 (47.4) months]. Patients were treated with oral CYC at the dosage of 50 mg/day, for consecutive 10-15 days monthly, for a mean of 63.8 (34.2) months, in association with oral prednisone at low (<10 mg/day; n = 9) or medium (> 10 mg/day; n = 13) doses. Results: The cumulative CYC dosage reached was 39 (28.7) g, (range 6-122). After the first year of therapy, differences with baseline results for diffusion lung capacity for carbon monoxide (DLCO) and forced vital capacity (FVC) were less than 15% and 10 % respectively, indicating that they remained almost stable. Moreover, in 13 patients who discontinued CYC, DLCO continued to improve more than 10% after 24 months, compared with baseline. In multivariate analysis, an improvement of more than 15% in DLCO after CYC discontinuation significantly correlated with limited cutaneous SSc, early disease, severe ILD, elevated acute phase serum proteins. HRCT documented a regression of ground glass (GG) pattern in 77% of patients. Decrease of GG was mostly detected in the first year of therapy (P < 0.01) and when GG was the predominant pattern. Disease activity estimated by European disease activity score, improved significantly after the first year (P < 0.01) and then stabilized during the follow-up. Medsger severity scale score remained overall stable. Modified Rodnan skin score remained unchanged. Ten out of 22 patients (45%) developed adverse events (reversible and no life-threathening) that require drug withdrawal in seven cases. Three patients died for not related drug causes. No side effects were reported after drug withdrawal. Conclusions: Oral CYC long-term therapy seem to be as effective as the intravenous pulse route and with comparable side effects. In our series, it ameliorated and/or stabilized lung function and HRCT pattern, maintaining favorable results after long time of discontinuation. Therapy was overall well tolerated with no severe adverse events. Disclosure of Interest : None Declared